Proceedings of the 2017 7th International Conference on Education, Management, Computer and Society (EMCS 2017) 2017
DOI: 10.2991/emcs-17.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Teaching and Research: Challenges and Solutions

Abstract: Abstract. Despite the urgent need of collaboration crossing disciplines in higher education, many challenges still exist, hindering the multidisciplinary work from going efficiently in practice. This essay describes difficulties faced by faculty members in interdisciplinary organizations on teaching and research. It illustrates that the "transaction cost" like lacking support, hard to get promoted in profession etc. for interdisciplinary faculties will be compensated if they get trained, gain diversity recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it can be said that some of the negative aspects expressed by participants stem from the challenging task of designing instruction aimed at an interdisciplinary approach and of transferring between branches, as stated by Savard and Samson (2014). Zhang (2017) emphasizes the difficulties of interdisciplinary collaborations and activities, especially in higher education, and attributes this to the weakness of close relationships, support and feeling of trust while conducting interdisciplinary studies or activities. The fact that pre-service teachers mention the negative aspects of interdisciplinary activities is due to their lack of complete knowledge of the interdisciplinary concept and the lack of knowledge in practice, as stated by Song (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it can be said that some of the negative aspects expressed by participants stem from the challenging task of designing instruction aimed at an interdisciplinary approach and of transferring between branches, as stated by Savard and Samson (2014). Zhang (2017) emphasizes the difficulties of interdisciplinary collaborations and activities, especially in higher education, and attributes this to the weakness of close relationships, support and feeling of trust while conducting interdisciplinary studies or activities. The fact that pre-service teachers mention the negative aspects of interdisciplinary activities is due to their lack of complete knowledge of the interdisciplinary concept and the lack of knowledge in practice, as stated by Song (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Montana-Hoyos and Lemaitre (2011) reported that the development of critical competencies and creativity are enhanced through integrative, collaborative, multidisciplinary, interdisciplinary (and hopefully transdisciplinary) instruction, and stated that integrative activities also develop the ability to establish new connections and relationships, which is a fundamental component of creativity. In a study, it was determined that the interdisciplinary learning experience improved the critical thinking ability of the students with the least competence (Zimmerman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%